Outside the "gender cages": men in training courses dedicated to educational and caring professions - Irene Biemmi (Firenze University Press, 2019)
This article deals with the lack of male enrolments in training courses dedicated to educational and caring professions. A study carried out by the author with male university students who have known how to move outside the "gender cages" by enrolling in broadly feminised courses of study, allows us to pinpoint a plurality of social and cultural factors that discourage young men from approaching knowledge and practices historically unrelated to their gender. This contribution also intends to highlight the lack of attention paid to the promotion of gender equality in the Italian school and training context, particularly in terms of educational orientation